Flavivirus Antagonism of Type I Interferon Signaling Reveals Prolidase as a Regulator of IFNAR1 Surface Expression - Lubick, Kirk J.; Robertson, Shelly J.; McNally, Kristin L.; Freedman, Brett A.; Rasmussen, Angela L.; Taylor, R. Travis; Walts, Avram D.; Tsuruda, Seitaro; Sakai, Mizuki; Ishizuka, Mariko; Boer, Elena F.; Foster, Erin C.; et al. (Cell host & microbe, 2015)
Type I interferon (IFN-α/β or IFN-I) signals through two receptor subunits, IFNAR1 and IFNAR2, to orchestrate sterile and infectious immunity. Cellular pathways that regulate IFNAR1 are often targeted by viruses to suppress the antiviral effects of IFN-I. Here we report that encephalitic flaviviruses, including tick-borne encephalitis virus and West Nile virus, antagonize IFN-I signaling by inhibiting IFNAR1 surface expression. Loss of IFNAR1 was associated with binding of the viral IFN-I antagonist, NS5, to prolidase (PEPD), a cellular dipeptidase implicated in primary immune deficiencies in humans. Prolidase was required for IFNAR1 maturation and accumulation, activation of IFNβ-stimulated gene induction, and IFN-I-dependent viral control. Human fibroblasts derived from patients with genetic prolidase deficiency exhibited decreased IFNAR1 surface expression and reduced IFNβ-stimulated signaling. Thus, by understanding flavivirus IFN-I antagonism, prolidase is revealed as a central regulator of IFN-I responses. [Display omitted] •TBEV and WNV inhibit surface expression of the interferon α/β (IFN-I) receptor, IFNAR1•The viral IFN antagonist NS5 binds to prolidase to prevent IFNAR1 surface expression•Prolidase is required for surface expression of IFNAR1•IFN signaling is compromised in fibroblasts from humans with prolidase deficiency Tick-borne encephalitis virus and West Nile virus antagonize type I interferon (IFN-I) signaling through unknown mechanisms. Lubick et al. demonstrate that prolidase promotes surface expression of the IFN-I receptor, IFNAR1, and is a target of viral antagonism. Further, prolidase deficiency in humans is associated with compromised IFN-I signaling.